Pengaruh Mulsa Organik Anyaman Daun Sawit Dan Interval Penyiraman Terhadap Pertumbuhan Bibit Sukun (Artocarpus communis) - Tria Yunita Sinaga; Budi Utomo; Yunus Afifuddin (Peronema Forestry Science Journal, 2016)
Degradation and deforestation of forest caused reduction vast and quality of forests. One of the solution to overcome this are reforestation and afforestation. Before replanting in the field needed seedlings with a good level of environmental adaptation that is by breeding improved varieties. Breadfruit is a plant that has a strong root system that can be a deterrent intrusion barriers to erosion and sea water. This research aims to get optimum organic mulch density and watering interval to growth of breadfruits. This research has done in green house at Agriculture Faculty of the University of North Sumatera (USU). The method used to analyze the effect of organic mulch woven palm leaf and watering interval to growth of breadfruits for 5 months. The observed parameter is height, diameter, number of leaves, leaves width, canopy width, length of roots, dry weight of  roots and moisture levels of leaves. Analysis data using the factorial complete random design (RALF). This research results showed that organic mulch woven palm leaves and watering interval significantly effect to growth of breadfruits except diameter parameter. Interaction of both aren’t significantly effect for all parameters. Keywords : Green house, breadfruits (Artocarpus communis), mulch.